The Effect of Insomnia on the Outcomes of Physical Therapy in Patients with Cervical and Lumbar Pain in Clinical Practice - Milan Djordjic; Aleksandra Jurisic Skevin; Vesna Grbovic; Ermin Fetahovic; Sofija Colovic; Milan Zaric; Tatjana Boskovic Matic; Olivera Radmanovic; Vladimir Janjic (Medicina)
Background and Objectives: The objective of the study is to determine whether there is a difference in physical therapy outcomes in patients with cervical and/or lumbar pain who have insomnia compared to patients without insomnia during a two-week period of active treatment under the conditions of routine clinical practice. Materials and Methods: The study population consisted of two groups of subjects with chronic back pain, a group with insomnia (“case”) with a total of 38 subjects and a control group without insomnia (“control”) with a total of 41 subjects, who filled out a set of measurement questionnaires: the McGill Pain Questionnaire and its short form (SF-MPQ), the Insomnia Severity Index (ISI) and the European Quality of Life Questionnaire of Life (Euro Qol; EQ-5D). Determination of the biomarkers of structural damage to the nervous tissue, neurofilament polypeptide (NEF—neurofilament polypeptide), neuron-specific enolase (NSE—neuron-specific enolase) and protein S100B was performed by measuring their concentrations in the blood using the ELISA method (enzyme immunosorbent assay). Statistical analysis of the collected data included a descriptive analysis, hypothesis testing methods and univariable and multivariable regression models. Results: At the end of the treatment visits, the level of pain remained higher in some subjects of the experimental group, but the statistical significance of the baseline difference disappeared because of the higher relative treatment response in the controls. Measured with a visual analogue scale, the treatment improved the patients’ quality of life much more in experimental than control subjects, as is proven by the statistically significant difference for the percent change from baseline (~31% vs. ~14%). At baseline, all three neurotropic biomarkers had significantly higher serum values in the subjects of the experimental group than in the control patients, which suggested more damage to the neuronal structures. During the treatment course, their serum concentrations decreased, from 36% to 95%, but for S100B, unlike NES and NEF, there was no statistically significant difference between the study groups at the end of the treatment visits. Conclusions: The results of the study have immediate scientific and practical significance because they contribute to new knowledge about the place and role of insomnia in patients with cervical and/or lumbar pain who are treated with physical medicine methods in the conditions of routine clinical practice. The treatment of insomnia should be an indispensable part of therapeutic treatment for patients with back pain.